Inefficient and unique processing of social–emotional interference in school-aged children with high-functioning autism spectrum disorder - Chen, Qing-Xin; Chen, Qi; Zhai, Kun; Chen, Hui-Ting; Wu, Yu-Lan; Liu, Jin-Ming; Jin, Yu (Frontiers in Psychiatry, 2024)
Interest grows in investigating the ability of processing social information under conflicting and complex environments in children with autism spectrum disorder (ASD), yet few studies have employed objective behavioral measures to explore the underlying profile of social-emotional interference control directly.In the current study, 53 children with ASD and 53 typically developing (TD) control aged 6-12 years completed a set of modified flanker tasks with arrow, schematic face, same real face (with facial interference by the same person) and different real face (with facial interference by different people), respectively. Response time in incongruent (RT Inc ) and congruent condition (RT Con ), percentage of error in incongruent (%Error Inc ) and congruent condition (%Error Con ), and flanker effect calculated by ΔRT = (RT Inc -RT Con ) / RT Con and Δ%Error = %Error Inc -%Error Con were used as outcome metrics.We obtained three major results: (1) ASD group had longer RT Inc and RT Con than the TD group in arrow, schematic face and same real face tasks; (2) compared with the performance in arrow flanker task, both groups exhibited longer RTs and reduced ΔRTs in the same real face task; however, in schematic face task, longer RT and reduced ΔRT were exhibited in the TD group, but not in the ASD group; (3) in the different real face task, ASD group had higher %Error than the TD group, and %Error was negatively correlated with RT only in the ASD group.The current study delineates the inefficient processing of social-emotional interference in school-aged children with ASD, and further suggests that they might adopt a relatively optimized strategy like symbolization when dealing with emotional conflict. However, such compensatory cognitive strategies may be exhausted along with the increase in information load. These findings provide new perspectives of considering the difference more than difficulty in the cognitive profile of ASD, which will benefit the development of targeted behavioral interventions.